„Czerwonym klinem bij Białych”. Żydowskie inspiracje El Lissitzky’ego - Kamczycki, Artur (Studia Europaea Gnesnensia, 2011)
The article focuses on the analysis of the 1919 poster entitled “Beat the Whites with the Red Wedge”. The intention of the text is to demonstrate the artist’s inspirations with Jewish mysticism, messianism and Kabbalah, exploited for the needs of the Soviet, revolutionary interpretation of building a new world.